DEVELOPMENT OF MODIFIED INJECTION PHANTOM AS A LEARNING MEDIA FOR INTRAVENOUS ACCESS INSERTION PRACTICUM IN NURSING LABORATORY - Luthfiati Putri, Eva; Suryanda; I Gusti Ayu Putu Desy Rohana (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Each laboratory is equipped with a phantom as a learning tool to support student practicum activities. Injection phantoms are essential for advancing students' knowledge and skills in performing injection procedures and installing intravenous access. However, the injection phantom in the Baturaja nursing laboratory does not meet the standard ratio of equipment to students. Additionally, the specifications and features of the existing phantom do not fully enhance students' practical experience. Therefore, the Educational Laboratory Institution needs to develop and modify the injection phantom learning tool as an alternative solution to meet the demand for practicum equipment. This research aims to develop and modify the injection phantom to fulfill the requirements of a learning tool that can enhance both the cognitive and psychomotor aspects of students during injection and intravenous access insertion practicum, using more cost-effective materials. This study employs the Research and Development (R&D) method, which includes the stages of design, tool assembly, initial trial, and subsequent tool acceptance or feasibility testing by expert validators. The sample consists of 40 participants, including 3 lecturers, 1 educational laboratory staff (PLP), and 36 students. The results indicate that the modified injection phantom functions effectively as a practicum learning tool in the laboratory and has a positive evaluation in terms of its appearance. Future research is expected to refine and further develop the function, as well as the overall and specific features, of the modified injection phantom.